2015
DOI: 10.1002/jssc.201501156
|View full text |Cite
|
Sign up to set email alerts
|

Multiple monolithic fiber solid‐phase microextraction based on a polymeric ionic liquid with high‐performance liquid chromatography for the determination of steroid sex hormones in water and urine

Abstract: The development of a simple and sensitive analytical approach that combines multiple monolithic fiber solid-phase microextraction with liquid desorption followed by high-performance liquid chromatography with diode array detection is proposed for the determination of trace levels of seven steroid sex hormones (estriol, 17β-estradiol, testosterone, ethinylestradiol, estrone, progesterone and mestranol) in water and urine matrices. To extract the target analytes effectively, multiple monolithic fiber solid-phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Among them, the use of functionalized PIL monolithic sorbent materials onto hollow-fiber supports of polyvinylidene fluoride (PVDF) [29] or polythene (PE) [30] has been reported. Furthermore, the use of multiple monolithic SPME fibers based on a PIL has also been recently reported, allowing the decrease of extraction times [31]. Chen et al developed a SPME fiber for HPLC based on the PIL obtained using the IL monomer 1-vinyl-3-hexadecylimidazolium hexafluorophosphate and polyhedral oligomeric silsesquioxane as crosslinker, mounted onto the surface of an anodized Ti wire [32].…”
Section: Introductionmentioning
confidence: 98%
“…Among them, the use of functionalized PIL monolithic sorbent materials onto hollow-fiber supports of polyvinylidene fluoride (PVDF) [29] or polythene (PE) [30] has been reported. Furthermore, the use of multiple monolithic SPME fibers based on a PIL has also been recently reported, allowing the decrease of extraction times [31]. Chen et al developed a SPME fiber for HPLC based on the PIL obtained using the IL monomer 1-vinyl-3-hexadecylimidazolium hexafluorophosphate and polyhedral oligomeric silsesquioxane as crosslinker, mounted onto the surface of an anodized Ti wire [32].…”
Section: Introductionmentioning
confidence: 98%
“…By crosslinking the PILs, the durability of the sorbent coating can be significantly enhanced, leading to a robust extraction system [13,[17][18][19]. Hybrid materials polymerized from an IL monomer and an organic/inorganic crosslinker have been applied as sorbent coatings for the analysis of various analytes in aqueous samples using SPME-HPLC [19][20][21][22]. A PIL-based monolith and its graphene oxide derivative were developed as SPME sorbent coatings for the analysis of polar endocrine disrupting chemicals and phenolic compounds with HPLC [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey showed that various SPME fibers coated with different types of materials such as polymeric sorbents [8,10,28], carbon materials [28][29][30], ionic liquids [28,31,32], and molecularly imprinted polymers [28,33,34] have been used in extraction of analytes. However, the most frequently used materials are polymeric sorbents [28].…”
Section: Introductionmentioning
confidence: 99%